Repetition, but Not Acoustic Differentiation, Facilitates Pseudohomophone Learning by Children. Issue 4 (2nd October 2022) - Conwell, Erin; Pichardo, Felix; Horvath, Gregor; Lopez, Amanda
ABSTRACT: Children's ability to learn words with multiple meanings may be hindered by their adherence to a one-to-one form-to-meaning mapping bias. Previous research on children's learning of a novel meaning for a familiar word (sometimes called a pseudohomophone ) has yielded mixed results, suggesting a range of factors that may impact when children entertain a new meaning for a familiar word. One such factor is repetition of the new meaning and another is the acoustic differentiation of the two meanings. This study asked 72 4-year-old English-learning children to assign novel meanings to familiar words and manipulated how many times they heard the words with their new referents as well as whether the productions were acoustically longer than typical productions of the words. Repetition supported the learning of a pseudohomophone, but acoustic differentiation did not.